Harmonisasi Hukum Islam dan Hak Asasi Manusia dalam Penanganan Nusyuz serta Kontekstualisasinya terhadap Hak Asasi Manusia - Seffin Granady; Khairul Mufti Rambe (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2026)
The concept of nusyuz originates from classical fiqh constructions and has evolved into a component of family law systems in several Muslim-majority countries. However, its classical formulation has frequently been criticized for potentially perpetuating unequal marital relations by legitimizing the husband's authority without systematically defined limitations. This situation raises concerns regarding the legal protection of wives from a human rights perspective. This study employs a doctrinal approach by examining legal principles, doctrines, and positive legal constructions concerning the limits of a husband's rights in addressing nusyuz. The analysis is conducted descriptively and critically through inductive and deductive reasoning to assess the potential abuse of authority and its juridical implications. The findings indicate that classical fiqh in fact contains normative limitations on the husband's actions, including the principles of gradual measures (tadarruj), the prohibition of harm, and the corrective purpose of sanctions. Nevertheless, these limitations have not been systematically formulated within a framework of marital partnership and the protection of human dignity. In the Indonesian context, any action that exceeds the principles of proportionality and non-violence may be classified as a legal violation, including criminal liability. This study affirms that the harmonization of Islamic law and human rights is achievable through reconstructing the limits of the husband's authority based on maqasid al-shariah, partnership principles, and the protection of women's life and dignity.